A cross-sectional study on the correlation between internal cerebral vein asymmetry and hemorrhagic transformation following endovascular thrombectomy - Lin, Kunxin; Zhao, Wenlong; Wu, Quanhong; Zheng, Yiru; Yang, Bo; Fu, Ying; Wang, Ning; Fang, Ling (Frontiers in Neurology, 2025)
IntroductionHemorrhagic transformation (HT) is a severe complication in patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO) after endovascular treatment (EVT). We hypothesize that asymmetry of the internal cerebral veins (ICVs) on baseline CT angiogram (CTA) may serve as an adjunctive predictor of HT.MethodsWe conducted a study on consecutive AIS-LVO patients from November 2020 to April 2022. These patients had anterior circulation occlusions and were treated with EVT. Asymmetrical ICVs were assessed using CTA and defined as hypodensity (reduced opacification) on the ipsilateral side of occlusion compared to the contralateral side. The primary outcome was HT, defined as hemorrhage within the ischemic territory. This was evaluated using follow-up imaging (CT scan or magnetic resonance imaging) performed 48 h post-EVT. HT was classified into four subtypes based on the European Cooperative Acute Stroke Study-II criteria.ResultsA total of 126 patients were included, with an HT rate of 49.2% (62/126). ICV asymmetry was observed in 54.0% (68/126) of patients. The ICV asymmetry group exhibited a significantly higher risk of parenchymatous hematoma-type HT (33.8% vs. 15.5%, p = 0.019) and symptomatic intracerebral hemorrhage (sICH) (23.5% vs. 5.2%, p = 0.004). In multivariate logistic regression, ICV asymmetry (OR 3.809, 95% CI 1.582–9.171), baseline Alberta Stroke Program Early CT Score (OR 0.771, 95% CI 0.608–0.978), intravenous recombinant tissue plasminogen activator (OR 2.847, 95% CI 1.098–2.7.385), and poor collateral circulation (OR 3.998, 95% CI 1.572–10.169) were identified as independent risk factors of HT.ConclusionICV asymmetry, likely resulting from impaired autoregulation or tissue micro-perfusion hampering cerebral blood flow (CBF), is a novel radiological sign that independently predicts HT. It is associated with a higher risk of sICH in AIS-LVO patients after EVT. Further research is warranted to validate these findings.